Toward Accurate Formation Routes of Complex Organic Molecules in the Interstellar Medium: The Paradigmatic Cases of Acrylonitrile and Cyanomethanimine - Barone, Vincenzo; Puzzarini, Cristina (Frontiers in Astronomy and Space Sciences, 2022)
The investigation of reaction mechanisms in the interstellar medium requires the evaluation of reaction rates and branching ratios, which can be effectively obtained in the framework of the ab-initio transition state/master equation formalism. However, the reliability of this approach relies on the computation of accurate reaction enthalpies and activation energies for all the paths characterizing the potential energy surface under investigation. Two effective yet reliable parameter-free model chemistries are introduced to obtain accurate energies of all stationary points, with structural determination performed using double-hybrid density functionals. After their validation, these model chemistries have been employed to analyze the competition between hydrogen abstraction and addition/elimination in the reaction between the CN radical and ethylene or methanimine. The energetics has then been complemented by a kinetic study. The results provide new information about important reactive channels operative in different regions of the interstellar medium and in the atmospheres of exoplanets. These further extend the recent general addition/elimination mechanism for the formation of "complex imines" from the reaction of methanimine with a small radical species.